Facile preparation and dual catalytic activity of copper(i)–metallosalen coordination polymers. Issue 39 (21st September 2015) - Hou, Yun-Long; Li, Sheng-Xia; Sun, Raymond Wai-Yin; Liu, Xin-Yuan; Weng Ng, Seik; Li, Dan
Abstract : Three copper(i )–metallosalen coordination polymers (CPs), [Ni II (SalImCy)]2 (Cu I CN)9 n (1 ), [Cu II (SalImCy)]2 (Cu I CN)9 n (2 ) and [Ni II (SalImCy)](Cu I I)2 ·DMF n (3 ) were prepared by direct combination of Ni II /Cu II (salen) motifs with [Cu I CN] n chains and Cu2 I2 clusters via the metalloligand strategy. Abstract : Three copper(i )–metallosalen coordination polymers (CPs), [Ni II (SalImCy)]2 (Cu I CN)9 n (1 ), [Cu II (SalImCy)]2 (Cu I CN)9 n (2 ) and [Ni II (SalImCy)](Cu I I)2 ·DMF n (3 ) were prepared by direct combination of Ni II /Cu II (salen) motifs with [Cu I CN] n chains and Cu2 I2 clusters via the metalloligand strategy. The mixed-valence and mixed-metal CPs could effectively catalyze both the oxidation of aromatic alcohols to ketones and aldehydes under mild conditions and photocatalytic degradation of organic dye methylene blue (MB). This work demonstrates the effective integration of transition metal catalytic Ni II /Cu II (salen) units and photoactive copper(i ) species in a single solid polymer to meet the demand for catalytic materials with the dual catalytic properties.